A Saga for dinner: landscape and nationality in Icelandic literature - Hennig, Reinhard (Universidad de Alcalá, 2011)
Iceland’s attempted industrialisation through an expansion of hydropower and aluminium smelters can lead to a significant reshaping of the country’s landscapes. There has been considerable resistance against such plans since the 1970s, culminating in the debate about the Kárahnjúkar project between 2001 and 2006. The book Draumalandið. Sjálfshjálparbók handa hræddri þjóð [Dreamland. A Self-Help Manual for a Frightened Nation] by the writer Andri Snær Magnason has been particularly influential. It combines ecological consciousness with an appreciation of Iceland‘s literary tradition and history. Thus it displays a view of landscape which connects nature preservation closely to cultural achievements and to national sovereignty. This perception of landscape originates from the assumption that Iceland experienced a golden age from the beginning of colonisation in the Viking age until the subordination under the Norwegian and later Danish kings in the 13th century, which led to an all-embracing degeneration. Nationalist poets such as Jónas Hallgrímsson in the 19th century based their demands for independence on Iceland‘s medieval saga literature and the country‘s landscapes. These seemed to provide evidence for a high culture in unity with nature during the time of the Commonwealth. Although the historical reliability of the sagas is doubtful, they are still used as an important argument in Draumalandið. Now the narratives as such are put in the foreground, as they can give value and meaning to the landscapes and places they describe. Thus a turn from a realistic to a more constructivist perception of landscape can be observed in contemporary Icelandic environmental literature. El intento de Islandia por industrializarse a través de la expansión hidroeléctrica y fundiciones de aluminio puede llevar a la reestructuración significativa del paisaje nacional. Existe una resistencia considerable a estos planes desde los 70`, culminando entre el 2001 y 2006 en el debate sobre el proyecto Kárahnjúkar. El libro ...